1986
DOI: 10.2527/jas1986.6341211x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Season and Social Environment on Testis Size and Semen Quality of the Adult Landrace Boar2

Abstract: Eight adult Landrace boars were housed for 12 mo in one of two social environments. Socially nonrestricted boars were penned adjacent to and allowed minimal physical contact with ovariectomized gilts hormonally induced into estrus every 2 wk. Socially restricted boars were penned behind solid walls to eliminate visual and physical contact with other pigs. All animals were subjected to natural changes in daylength. Semen was collected weekly; gel-free volume, gel weight, sperm concentration and number per ejacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 0 publications
4
35
0
Order By: Relevance
“…Volume was the only characteristic that was higher during the decreasing period, in agreement with the studies of Trudeau and Sanford (1986) and Knecht et al (2013), who studied photoperiod. However, they contrast with Greenberg and Mahone (1981) and Sancho et al (2004), who, working with an artificially induced photoperiod, observed an increased volume with increasing day length.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Volume was the only characteristic that was higher during the decreasing period, in agreement with the studies of Trudeau and Sanford (1986) and Knecht et al (2013), who studied photoperiod. However, they contrast with Greenberg and Mahone (1981) and Sancho et al (2004), who, working with an artificially induced photoperiod, observed an increased volume with increasing day length.…”
Section: Discussionsupporting
confidence: 78%
“…Temperature and photoperiod show the most important effects on pigs (Kozdrowski and Dubiel, 2004;Rivera et al, 2005). It is suggested that photoperiod may play an important role, especially in temperate climates, due to the significant differences in day length over the year (Kunavongkrit et al, 2005 Sperm volume and concentration are lowest in the spring; they gradually increase during the summer, and reach a peak in late autumn (Trudeau and Sanford, 1986;Borg et al, 1993;Kozdrowski and Dubiel, 2004). Changes in the photoperiod cause variations in semen production (Mazzarri et al, 1970) and volume, and spermatozoa abnormalities (Sancho et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These results in conformity with data published by Ciereszko et al [9] and Trudeau and Sanford [29] , who analyzed ejaculates in relation to the season of semen collection. According to Knecht et al [6] , a high sperm concentration in ejaculates collected in winter results from lower temperatures, which has a positive effect on spermatogenesis.…”
Section: The Data Presented Insupporting
confidence: 81%
“…This could be a consequence of lesser fertilized abilities (Tarocco, 1990) by nontreated boars. In boars, seasonal changes, and particularly temperature and photoperiod, directly affect the steroid production (Trudeau and Sanford, 1986;Levis, 1998;Park and Yi, 2002). Testosterone level was not affected by treatment (C=5.51 ng/ml; T=7.32 ng/ml).…”
Section: Effect Of Dietary Administration Of Oil Extract From Rosemarmentioning
confidence: 89%
“…The motility of sperm was estimated on a drop of fresh semen, at 37°C by light microscope at 80X, assigning to each reading a 0 to 5 score. Detection of live and abnormal spermatozoa was evaluated by phase contrast microscopy at 1000X (Superchi et al, 1998) on 150 sperm per sample. At 0, 45 and 90 d from the beginning of treatment, blood samples were collected, at 10.00 a.m., via jugular vein venipuncture in tubes without anticoagulant.…”
Section: Effect Of Dietary Administration Of Oil Extract From Rosemarmentioning
confidence: 99%